Clinico-Epidemiologic Profile of Non-Syndromic Congenital Ichthyosis – A Retrospective Chart Review of 107 Patients - Rahul Mahajan; Shirin Bakshi; Debajyoti Chatterjee; Dipankar De; Uma N. Saikia; Sanjeev Handa (Indian Journal of Dermatology, 2024)
Background: Congenital ichthyoses are a rare Mendelian group of disorders affecting the integument with a heterogeneous clinical presentation amongst which scaling is a constant feature. There is scanty epidemiologic data regarding the clinical profile and histologic patterns of inherited ichthyosis from resource-poor countries. Aims and Objectives: The study was aimed at assessing the clinic-epidemiologic characteristics associated with the different forms of non-syndromic congenital ichthyosis. Materials and Methods: This was a retrospective chart review of ichthyosis patients that presented between July 2016 and Jun 2020. Details including demographic profile, clinical characteristics along with any relevant investigations done were included. Results: During the study period of 4 years, 107 patients with congenital non-syndromic ichthyosis were seen. The most frequent diagnosis was of common ichthyoses, followed by autosomal recessive congenital ichthyosis, epidermolytic ichthyosis and erythrokeratoderma, in decreasing order. Conclusion: Important clinical findings like erythema and the type of scales as well as histological differences including an absent or reduced granular layer in ichthyosis vulgaris can help differentiate among the clinical phenotypes of inherited non-syndromic ichthyosis especially in resource-poor settings. Also, there is a high prevalence of vitamin D deficiency and hence a need for screening for the same in all patients of congenital ichthyosis including the milder phenotypes.